Traditional Methods of Dealing with Conflicts among IDPs in Duhok Governorate in Iraqi Kurdistan; including a case study of Yesidi mediators - Mohammed, Maamoon Abdulsamad; Sadeeq, Zerevan S.; Abdullah, Jehan A.; Kamali, Sanaz (Humanities Journal of University of Zakho, 2018)
The recent influx of internally displaced people (IDPs) into Kurdistan Region-Iraq with little hope of returning home has made peaceful coexistence within and between religious groups (both in host communities and IDP camps) a priority for local and international bodies. However, in Iraq, minority groups’ cultural norms lack representation in national laws and practices which are based in Islamic traditions and sometimes contradict minority religions’ customs and beliefs. This serves to undermine their traditions’ ability to confer the dignity and positive identity essential to a peaceful, stable society, and even to erode those traditions themselves to the point of extinction. Nevertheless, the practice of traditional methods of conflict resolution has shaped social interactions, bridging social divisions and enabling the mending of broken relations within and among groups. Based on a collaborative project (GIZ-funded and implemented by forumZFD and the University of Duhok in 2016) to promote social cohesion and identify conflict-resolution methods used by religious groups in six camps near Duhok, this paper focuses specifically on those of the Yesidiz. This religious group comprises about 85% of IDPs in the area and tends to experience most resentment in their adopted neighbourhoods; however, their use of traditional methods was found to be higher than other groups. Yezidi mediators include middle level and grassroots actors, making them well placed to be effective in peacebuilding because of their extensive interaction with disputing parties and their capacity to constantly adapt traditional methods to situations. After discussing the methods used generally by displaced religious minorities, the paper presents the characteristics of Yezidi mediators and concludes that these methods are essential to developing sustainable peace because Yezidis in Kurdistan are proud to conform to them, hence, helping to improve understanding and reduce resentment. KEYWORDS: Mediator, Traditional methods, IDPs, Conflict, Conflict resolution